Vinorelbine as a radiosensitizer in Pakistani patients with locally advanced unresectable head & neck cancer (HNC) in tertiary care hospital of Pakistan - Khan, Rana Atique Anwer; Masood, Ahmed Ijaz; Gorchani, Sadaqat Ali; Muhammad Junaid; Khan, Ali Yasir (International Journal of Endorsing Health Science Research, 2019)
Background: Head and neck cancer (HNC) is one of the most common cancers in Pakistan. Disease free survival in HNC remains poor due to inefficient loco-regional disease control. The aim of the present study was to assess the response rate and toxicity of concomitant vinorelbine and External radiation therapy (ERT) in advanced Head and Neck cancer in local Pakistani population. The study as per Good Clinical Practice (GCP) guidelines was conducted at the oncology department of Nishat hospital Multan from 2015 to 2017. Methodology: An observational, prospective study with enrollment of 50 patients of advanced head and neck cancer was followed to analyze the outcome for radiosensitization. Primary tumor sites were tongue in 15 (30%) patients; lower lip in 6 (12%); buccal cavity in 5 (10%); cheek in 5 (10%); tonsil in 4 (8%); larynx in 6 (12%); hypopharynx in 5 (10%); and parotid in 4 (8%) patients. Initial clinical stage was: IV in 23 (46%) patients and III in 27 (54%) patients. Vinorelbine (VNB) was given at dose of 10 mg i.v. infusion weekly with ERT (3D conformal radiation plan). Response rate was evaluated after at least 8 doses. Response evaluation criteria in Solid Tumors (RECIST) was used to assess complete response (CR) and partial response (PR); progressive disease (PD) and stable disease (SD). Toxicity was assessed using common toxicity criteria version 3.0 (CTCV3.0). Results: 44 out of 50 patients were evaluable for response rate and toxicity. Immediate response was 90% CR. After 24 months of followup CR, PR, SD, and PD were seen in 26 (59%), 6 (13%), 7 (15%) and 6 (13%) patients respectively. Grade III mucositis and dysphagia were observed in 19 (43%) and 8 (18%) patients respectively, grade III skin rash in 14 (30%) patients, grade-II peripheral neuropathy was seen in 3 (6%) patients. Conclusion: The study showed that vinorelbine as a radiosensitizer in advanced HNC is a feasible option with acceptable toxicities. A large study is required to define its definite role.